For the creative portrait of David Turdospireli - Kochloshvili, Nino ("Intercultural Dialogues" Transactions, 2025)
In the literary heritage of Davit Turdospireli, we find very interesting examples of miniature prose. Among the creators of Georgian short prose, he is a writer with his own voice. In Turdospireli's short prose works, along with a number of features characteristic of the genre specificity, the stylistic manner of the writer is interestingly revealed. His miniatures are distinguished by the individuality of the narrative. First of all, what attracts the reader's attention is the pale epic embroidery of the miniatures, which is entirely built on mood. The writer's spiritual feelings are conveyed with amazing lyricism and high artistic skill in a variety of original tropical speech. The poetics of Davit Turdospireli's miniatures are often fueled by the writer's insatiable spiritual pain, which his difficult life left him with as a constant companion. The pessimistic feelings caused by his difficult life did not only permeate Davit Turdospireli's autobiographical memories, but also infused a sad mood into the writer's literary heritage. Especially in the short prose works created in the first half of the twentieth century, which interestingly present the writer's literary portrait. Despite the strict canons of short prose, Davit Turdospireli manages to convey subjective feelings to the reader with rare writing skill; directness and sincerity are the characteristics of his artistic thinking. The artistic space of Davit Turdospireli's miniatures is boundless. The writer takes us on a journey through the past and the present almost simultaneously, and no matter how surprising it may be, he almost always finds spiritual closeness with the "withered leaves", "fog", "abundant night", "dying autumn flowers", "autumn twilight", "sad night". The writer, despite everything, does not give in to pessimism, looking with the eyes of hope at the sight that has crept into the bosom of the soul like a breeze to whisper the tale of eternal spring. The fairy tales of the Ankara stream flowing from the mountain peaks on the airy mists of the sky hope for the fulfillment of magical, dreamy dreams. Already the human race also hopes and warns man, the face of life and love, not to treat spring with disdain, perhaps thanks to it he can somehow save his faith in existence.